Implementation the Strengthening of Character Education through Social Studies Learning and School Culture - Ahmad Tanfidzi Dharma Putra; Harmanto Harmanto; Aminuddin Kasdi (Universitas Negeri Surabaya, 2021)
Character development and intellectual enhancement of students were important and prioritized in the national education system in Indonesia. The purpose of this research was to explain and find out the results of implementation the Strengthening of Character Education (SCE) through social studies learning and school culture at Junior High School Sunan Giri Menganti Gresik. This research was qualitative research based on a case study. The research was conducted in September-December 2020 with the subjects were school principals, vice principals in curriculum, social studies teachers, and school members. Data collection techniques was interviews, documentation, field notes, and observations. Data analysis used three methods, there were data reduction, presentation of data results, and conclusions. The results showed that implementation the SCE at Junior High School Sunan Giri Menganti in social studies learning written in the RPP based on the 2013 Curriculum reference and in school culture through classroom management, Islamic culture, mutual cooperation and discipline, home visit, National Day Celebration, and Islamic Day Celebration.